Risks and new challenges in the food chain: Viral contamination and decontamination from a global perspective, guidelines, and cleaning. Issue 2 (10th February 2022) - Ezzatpanah, Hamid; Gómez‐López, Vicente Manuel; Koutchma, Tatiana; Lavafpour, Farnoush; Moerman, Frank; Mohammadi, Mohammad; Raheem, Dele
Abstract: Even during the continuing world pandemic of severe acute respiratory syndrome coronavirus 2 (SARS CoV‐2), consumers remain exposed to the risk of getting infected by existing, emerging, or re‐emerging foodborne and waterborne viruses. SARS‐CoV‐2 is different in that it is transmitted directly via the airborne route (droplets and aerosols) or indirect contact (surfaces contaminated with SARS‐CoV‐2). International food and health organizations and national regulatory bodies have provided guidance to protect individuals active in food premises from potential occupational exposure to SARS‐CoV‐2, and have recommended chemicals effective in controlling the virus. Additionally, to exclude transmission of foodborne and waterborne viruses, hygiene practices to remove viral contaminants from surfaces are applied in different stages of the food chain (e.g., food plants, food distribution, storage, retail sector, etc.), while new and enhanced measures effective in the control of all types of viruses are under development. This comprehensive review aims to analyze and compare efficacies of existing cleaning practices currently used in the food industry to remove pathogenic viruses from air, nonfood, and food contact surfaces, as well as from food surfaces. In addition, the classification, modes of transmission, and survival of food and waterborne viruses, as well as SARS‐CoV‐2 will be presented. The international guidelines and national regulations are summarized in terms of virucidal chemical agents and their applications.